Regulation of salt tolerance in the roots of Zea mays by L-histidine through transcriptome analysis - Ji, Hongfei; Yang, Guoping; Zhang, Xiu; Zhong, Qiumei; Qi, Yuxi; Wu, Kaihua; Shen, Tingting (Frontiers in Plant Science, 2022)
Soil salinization is an important worldwide environmental problem and the main reason to reduce agricultural productivity. Recent findings suggested that histidine is a crucial residue that influences the ROS reduction and improves the plants’ tolerance to salt stress. Herein, we conducted experiments to understand the underlying regulatory effects of histidine on maize root system under salt stress (100 mM NaCl solution system). Several antioxidant enzymes were determined. The related expressed genes (DEGs) with its pathways were observed by Transcriptome technologies. The results of the present study confirmed that histidine can ameliorate the adverse effects of salt stress on maize root growth. When the maize roots exposed to 100 mM NaCl were treated with histidine, the accumulation of superoxide anion radicals, hydrogen peroxide, and malondialdehyde, and the content of nitrate nitrogen and ammonium nitrogen were significantly reduced; while the activities of superoxide dismutase, peroxidase, catalase, nitrate reductase, glutamine synthetase, and glutamate synthase were significantly increased. Transcriptome analysis revealed that a total of 454 (65 up-regulated and 389 down-regulated) and 348 (293 up-regulated and 55 down-regulated) DEGs were observed when the roots under salt stress were treated with histidine for 12 h and 24 h, respectively. The pathways analysis of those DEGs showed that a small number of down-regulated genes were enriched in phytohormone signaling and phenylpropanoid biosynthesis at 12 h after histidine treatment, and the DEGs involved in the phytohormone signaling, glycolysis, and nitrogen metabolism were significantly enriched at 24 h after treatment. These results of gene expression and enzyme activities suggested that histidine can improve the salt tolerance of maize roots by enriching some DEGs involved in plant hormone signal transduction, glycolysis, and nitrogen metabolism pathways.